Understanding the commitment efficiency, process and influence of journalism professionalism practices amongst web newspaper journalists in Saudi Arabia / Saleh Zaid S Alenizi - S Alenizi, Saleh Zaid (Institute of Graduate Studies, UiTM, 2014)
The phenomenon of web journalism in the Kingdom of Saudi Arabia is one of the new practices in Saudi journalism. Despite the newness of this journalistic phenomenon, a number of Saudi web newspapers (more than 250 web newspapers according to a mini¬survey conducted to determine the number of Saudi web newspapers) differs in terms of their ideological and professional orientations. There are web newspapers that cover specific regions in Saudi Arabia, web newspapers specializing in a given topic such as sports, children, women, business web newspapers, as well as general web newspapers that cover various topics.